Liraglutide Alleviates Hepatic Steatosis and Liver Injury in T2MD Rats via a GLP-1R Dependent AMPK Pathway - Zhou, Rui; Lin, Chuman; Cheng, Yanzhen; Zhuo, Xiaoyun; Li, Qinghua; Xu, Wen; Zhao, Liang; Yang, Li (Frontiers in Pharmacology, 2021)
Non-alcoholic fatty liver disease (NAFLD), ranging from non-alcoholic fatty liver to non-alcoholic steatohepatitis, can be prevalent in patients with type 2 diabetes mellitus (T2DM). However, no antidiabetic drug has been approved for the treatment of NAFLD in T2DM patients. Multiple daily injections of basal-bolus insulin are often the final therapeutic option for T2DM. We found that insulin treatment aggravated hepatic steatosis and oxidative stress in Zucker diabetic fatty (ZDF) rats. In addition to glycaemic control, we demonstrated the stimulatory role of liraglutide in relieving hepatic steatosis and liver injury in ZDF rats. Interestingly, liraglutide could also alleviate insulin-aggravated hepatic fatty accumulation. The glucagon-like peptide-1 (GLP-1) agonists liraglutide and Ex-4 activated the expression of peroxisome proliferator-activated receptor alpha (PPARα) via a GLP-1 receptor-dependent 5′ AMP-activated protein kinase pathway. As a nuclear transcription factor, PPARα could mediate the effect of GLP-1 in alleviating hepatic steatosis by differentially regulating the expression of its target genes, including acetyl CoA carboxylase and carnitine palmitoyl transferase la both in vitro and in vivo. Moreover, GLP-1 could relieve liver injury by decreasing oxidative stress stimulated by hepatic steatosis. Insulin might aggravate hepatic steatosis and liver injury by inhibiting GLP-1R expression. The findings indicate the feasibility of liraglutide treatment combined with basal insulin in attenuating hepatic steatosis and liver injury in ZDF rats. This knowledge, and the evidence for the underlying mechanism, provide a theoretical basis for the combination treatment recommended by the latest clinical practice guidelines for T2DM.